Ryzyko inwestycji w obligacje komunalne w Polsce - Kozuń-Cieślak, Grażyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The municipal bonds'market is the peculiar segment of the debt scurities' market. Because of the special local government's status as an issuer, municipal bonds possess the rank of the public debt and they are perceived as low risk scurities. However it doesn't mean, that investing in municipal bonds is risk - free. Commonly enumerated risk factors generally applied to investing in bond are also applied to bonds issued by local government entities. The market of municipal bonds in Poland is relatively young and it is not completely formed, particularly in the area of secondary circulation. Moreover it is necessary to remember that Poland isn't the country of the mature market economy still. It is resulting in variability of economic conditions - with the instable legal system, numerous interventions of monetary and fiscal authorities, sensitivity to the interaction of the foreign capital. Above-mentioned factors are increasing the investment risk significantly in Poland. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 1, s. 279-287